Learning Strategies at SD Muhammadiyah 3 Pandaan During Covid-19 Pandemic - Fania Amanda Islamy; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2021)
The study describes the current learning strategy that utilitizes technological technological advances during the Covid-19 pandemic at SD Muhammadiyah 3 Pandaan. The use of modern technology is currently useful in learning namely online learning. In the research process using data collection techniques through interviews, observation, and using a voice recorder during the research process. This research study aims to determine the use of learning strategies and obstacles or challenges during the covid 19 pandemic at Sd Muhammadiyah 3 Pandaan. In the implementation of learning currently using learning media where the learning is done virtually or online in the form of YouTube, google meet, zoom meeting, and etc. with the covid 19 pandemi, teachers and students can use information technology well so that teaching and learning activities run optimally and add additional experience in the future.